2016
DOI: 10.1155/2016/1327265
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Nonsustained Ventricular Tachycardia in Patients with Pulmonary Hypertension

Abstract: Background. Increased pulmonary vascular resistance in patients with pulmonary hypertension (PH) leads to an increased afterload of right heart and cardiac remodeling which could provide the substrate or trigger for arrhythmias. Supraventricular arrhythmias were associated with clinical deterioration but were not associated with sudden cardiac death (SCD). SCD has been reported to account for approximately 30% of deaths in patients with pulmonary arterial hypertension (PAH). Objective. The role of nonsustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…16,17 In accordance with the results of studies evaluating supraventricular arrhythmias, TAPSE was reduced in patients with nsVT 16,17 and cardiac index was reduced, whereas PVR, sPAP, and mPAP were elevated. 16,17 The authors' study showed that extending Holter ECG monitoring to longer than 24 hours raised the detection rate of arrhythmias. 17 The main result of the study was that the prognostical relevance of nsVT was missing.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…16,17 In accordance with the results of studies evaluating supraventricular arrhythmias, TAPSE was reduced in patients with nsVT 16,17 and cardiac index was reduced, whereas PVR, sPAP, and mPAP were elevated. 16,17 The authors' study showed that extending Holter ECG monitoring to longer than 24 hours raised the detection rate of arrhythmias. 17 The main result of the study was that the prognostical relevance of nsVT was missing.…”
Section: Discussionsupporting
confidence: 75%
“…Only a few studies have evaluated the incidence and clinical relevance of non-sustained ventricular tachycardia in patients with PH ( Table 2). [16][17][18] Bandorski et al investigated 92 patients with PH (groups 1, 3-5) without a known history of preexisting arrhythmias. 17 Functional class was NYHA III/IV in 70.6%.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…The current standard of medical care consists of periodic ambulatory clinic visits with testing including echocardiography, exercise testing, and monitoring for arrhythmia. While these tests provide useful information about cardiac function, they neither correlate with overall debility; nor do they adequately predict risk of future adverse events [36][37][38][39]. Knowing that debilitating morbidities are not limited to only specific cardiac conditions, the intention of this study was to develop a broad based, generalizable clinical measure of infirmity for children and adolescents with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…It highlighted that the use of Holter monitoring in this cohort was beneficial for arrhythmia diagnosis and this may be a useful tool in PAH patients also. To determine the prognostic significance of NSVT Bandorski et al (25) examined 78 patients with PAH or inoperable CTEPH. Fifty-Five patients with PAH and 23 CTEPH underwent a clinical review, bloods, Holter monitoring, 6 MWT, echocardiography and RHC (25), of whom 12 had newly detected NSVT.…”
Section: Cardiac Arrhythmias: Classification and Mechanismmentioning
confidence: 99%